Bioelectrical impedance spectroscopy measuring the magnitude of body water compartment changes pregame and postgame in collegiate ice hockey players - Heesch, A. J.; Otremba, J. R.; Morgan, R. M.; Montgomery, B. M.; Poolman, M. A.; Schindler, G. D.; Fitzgerald, J. S. (The Journal of Strength and Conditioning Research, 2025)
Bioelectrical impedance spectroscopy (BIS) is an accurate and feasible measure of hydration and compartment water, although its ability to detect meaningful changes in field settings is unknown. This study evaluated the typical changes in whole-body and segmental body compartment water before and after games in 25 male National Collegiate Athletic Association Division I ice hockey players using a SOZO BIS device. Measurements were taken the mornings of and the mornings after the first game of a two-game series across 9 home games. Absolute changes at the individual level were averaged for each game and across games to estimate typical changes in body water. Medium total body water loss (mean change [95% CI]: -0.63 L [-0.80 to -0.37]; percent change: 1.2%), large extracellular water loss (mean change [95% CI]: -0.56 L [-0.73 to -0.39]; percent change: 2.5%), and small leg intracellular water loss (mean change [95% CI]: -0.12 L [-0.23 to -0.01]; percent change: 1.1%) were still present in the morning after the game. These findings indicate that BIS is sensitive to small changes in whole-body and leg segment body water compartments at the group level in an ecologically valid sports setting, and the body water compartment losses observed in this study emphasize the importance of effective postgame rehydration strategies. Hypohydration is linked to meaningful end points in sport (e.g., exercise performance, heat illness, recovery), and the ability to noninvasively monitor whole-body and segmental compartment water with BIS may improve sport staff's ability to implement effective hydration and nutrition strategies for athletes.